Tuberculosis and COVID-19: A Tale of Two Illnesses - Noella Maria Delia Pereira (Pediatric Infectious Disease)
Tuberculosis (TB) and COVID-19 are both primarily respiratory illnesses that can be prevented. This article aims to compare and contrast the transmission of both illnesses. We also study the differences in public health approaches to help prevent their transmission and spread. While COVID-19 can be prevented by lockdowns and quarantine, these may not be feasible to prevent the spread of TB. Contact tracing, treating contacts of TB patients with TB preventive therapy in children below 5 years as well as in the immunocompromised population, can help prevent the spread of the illness.